Analysis of geographic and orographic influence in Spanish monthly precipitation. (31st January 2017) - Álvarez‐Rodríguez, J.; Llasat, M. C.; Estrela, T.
ABSTRACT: Precipitation is a major concern in water resources studies. Being a main variable, the inefficiency of historical ground network, particularly at higher altitudes where precipitation and runoff augmentations are expected, constitutes a major drawback. This work analyses the competence of Spanish historical precipitation network and explores the physiographic influence of elevation and orientation at a national scale. The usefulness of slopes is also explored. Nearly 12 000 monthly precipitation series recorded from the 19th century until the hydrological year 2004/2005 over a high‐resolution topographic map (200 m) of Spanish territory are used. Comparable statistics and precipitation lapse rates are managed once a completion of gaps is accomplished. Then, Spanish yearly rates range from 0.3 to 1.2 mm m −1, reaching 1.5 mm m −1 in Northern Iberian Peninsula, diminishing at highest altitudes. Conclusions address the inefficiency and uncertainties revealed by historical ground networks as well as the variable relationship existing between precipitation and physiographic parameters, such as altitude and orientation.